Ugandan crater lakes: inferring hydrological change using stable isotopes - Hunt, Laura Hazel (2023)
A group of >80 crater lakes associated with the East African Rift System in western Uganda provide important water resources to rural communities, alongside opportunities for aquaculture and tourism. The lakes are impacted by, and face increasing pressure from human activities such as land use change and climate change. These issues are exacerbated by the region’s high population growth rate and low levels of water infrastructure. To help inform future management of the lakes, this research aimed to understand the hydrology of the crater lakes, their sensitivity to hydroclimate forcing, and the nature and drivers of hydrological change over the past few centuries. In this thesis contemporary lake water isotope data from the region and isotope mass balance models are used show that while the lakes are generally evaporative systems sensitive to changes in the ratio of precipitation to evaporation, groundwater forms a substantial proportion of the hydrological budgets. This is particularly the case in two of the study sites, Lakes Kasenda and Nyungu. Sensitivity analysis of the isotope mass balance models show that Lake Kasenda, which is volumetrically smaller and has a shorter lake water residence time, with a smaller proportion of their hydrological budgets comprised of groundwater, is more sensitive to climate forcing then Lake Nyungu. In the absence of long-term limnological monitoring, authigenic carbonate